Experimental investigation of top burr formation in high-speed micro-milling of Ti6Al4V alloy. (March 2020) - Kumar, Mohan; Bajpai, Vivek
Miniaturization with superior quality product of super alloy is the demand of the industry. Ti6Al4V is the demanding super alloy due to its excellent material properties, although this super alloy is known for poor machinability in terms of burr formation, low tool life, and poor surface finish. Therefore, being a popular super alloy, it comes under the difficult-to-cut material. In the current work, burr formation on the machining of Ti6Al4V has been studied. Experimental investigation and characterizations of top burr formation on Ti6Al4V alloy using end milling process were carried out. A scanning electron microscopy identifies the burr formed on the machined surface. A new technique has been introduced to measure the top burr width (i.e. equivalent width) accurately. Equivalent burr width calculated as the ratio of total area of burr generated to the total height. It was observed that equivalent burr width in up milling was increased by 120%, while in down milling, it was decreased by 50% as the speed varies from conventional to high speed. Furthermore, the effects of different cutting parameters and tool parameters on top burr formation have been analyzed to establish correlation among them.